Social psychology meets online information diffusion - Li, Hui (Nanyang Technological University, 2022)
Social networks provide online platforms for individuals to express their opinions and interact with others, and thereby generate huge volumes of social activities (e.g. tweets, retweets, comments, like). Such social activities give rise to online information diffusion. Hawkes processes, in which the social event arrival rate explicitly depends on previous events, is a well-known statistical technique utilized to model information diffusion. However, existing information diffusion framework are oblivious to the impact of social psychology (e.g. conformity) on the diffusion process. In this thesis, we explore the interplay between conformity of individuals and online information diffusion under the framework of Hawkes processes. Intuitively, conformity refers to the inclination to align our attitudes and behaviors with those around us.